Respon Spektral Tajuk Jagung pada beberapa Perlakuan Pemupukan: Spectral Response of Maize Canopy to Several Fertilization Treatments - Muhammad Ardiansyah; Budi Nugroho; Arival Al-Fajar (Jurnal Ilmu Tanah dan Lingkungan, 2022)
Early detection of plant nutrient status during the maize cycle is important to prevent yield loss and to optimize yield and quality. This study was conducted to analyze the spectral response of the maize canopy to 10 fertilization treatments including control using a spectroradiometer. In this study, the relationship between nutrient content and spectral response was focused on leaf N levels, which were analyzed at 4 and 8 weeks after planting (WAP). Simple and multiple linear regression models were developed to study this relationship, both models based on wavelength spectrum and selected wavelength to see the relationship between spectral reflectance and leaf N content. In general, the spectral response pattern of maize canopy for each treatment at 4 and 8 WAP was similar, where the reflectance of 4 WAP being lower than 8 WAP for all wavelengths. Leaf N levels could be identified at the green wavelength of 555 nm, which was indicated by the lowest reflectance at 4 WAP and high at 8 WAP for treatment of 1 standard (STD) or the highest N dose. The low reflectance of the 555 nm wavelength of this treatment indicated that the N content in the leaves was higher at 4 WAP than 8 WAP. The red, green, and red-edge wavelengths at 4 WAP and 8 WAP showed a moderate to very strong relation with leaf N content with a coefficient of determination (R2) greater than 0.40. The very strong model was shown by the multiple regression model between the combination of blue, green, red, red-edge, and near-infrared spectrum for leaf N levels for both 4 WAP and 8 WAP. The selected wavelength-based model found that the relationship was very strong shown by the wavelength of 671 nm.